2020
DOI: 10.1016/j.rsma.2020.101109
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of horn snail Telescopium telescopium (Linnaeus C, 1758) using mt-COI gene sequences

Abstract: We aimed to apply DNA barcoding tool for the molecular identification of horn snails T. telescopium using mitochondrial cytochrome oxidase I gene (mt-COI) and to investigate their evolutionary relationship along with location-specific bio-geographical variations. The molecular data sets of this study indicate that strong probability of T. telescopium species taxonomic confirmation using mt-COI sequences. Results of the phylogenetic analysis suggest that Telescopium sp. was monophyletic with disseminated nodes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…Previous nationalised efforts to barcoding the marine diversity (Lakra et al, 2010;Bineesh et al, 2014;Bamaniya et al, 2015) along with localised efforts to barcode the diversity of Vellar estuary (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Sahu et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020;Narra et al, 2020) resulted in strengthening the reference library which insured that no ambiguous sequences were present in this study (as all sequences were identified to species level). Identification success was likely due to the use of previously generated references sequences from Indian waters from morphologically verified species and published through reference databases (such as GenBank and BOLD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous nationalised efforts to barcoding the marine diversity (Lakra et al, 2010;Bineesh et al, 2014;Bamaniya et al, 2015) along with localised efforts to barcode the diversity of Vellar estuary (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Sahu et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020;Narra et al, 2020) resulted in strengthening the reference library which insured that no ambiguous sequences were present in this study (as all sequences were identified to species level). Identification success was likely due to the use of previously generated references sequences from Indian waters from morphologically verified species and published through reference databases (such as GenBank and BOLD).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to capture potential genetic variation, including undocumented cryptic diversity, it is important to sequence an adequate number of individuals from across a species range (Weigt et al 2012b). We have made considerable efforts in the past decade as part of the Indian Census of Marine Life (ICoML) to recover barcodes in reasonable numbers of marine phyla including fin & shell fishes, invertebrates (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020) and plants (Sahu et al, 2016;Narra et al, 2020) occurring in and around the Vellar estuary. Hence we predict a high rate of success in identification of dietary items of A. maculatus occurring in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…Identifikasi dengan pendekatan molekuler telah banyak dilakukan pada beberapa jenis gastropoda seperti Turbinidae [3], Turbo sp. [13], Telescopium telescopium [14].…”
Section: Pendahuluanunclassified
“…This study used COI gene from mitochondrial DNA as the target gene. The COI genes showed a global bio identification system of animals, a universal primer for a very strong COI gene (Palanisamy et al 2020), and have a greater range of phylogenetic signals than other mitochondrial genes (Sutrisno 2015). This method, however, needs species-specific primers enabling the authentication of products from particular species.…”
Section: Introductionmentioning
confidence: 99%